2016
DOI: 10.18632/oncotarget.11342
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic effects and mechanisms of micheliolide in acute myelogenous leukemia stem cells

Abstract: Leukemic stem cells (LSCs) greatly contribute to the initiation, relapse, and multidrug resistance of leukemia. Current therapies targeting the cell cycle and rapidly growing leukemic cells, including conventional chemotherapy, have little effect due to the self-renewal and differentiated malignant cells replenishment ability of LSCs despite their scarce supply in the bone marrow. Micheliolide (MCL) is a natural guaianolide sesquiterpene lactone (GSL) which was discovered in michelia compressa and michelia cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…DMAMCL is a novel agent that has an effect of anti-tumor growth and anti-inflammation. DMAMCL reduces tumor proliferation in glioma cells in vitro and in vivo [23], and selectively deracinates AML stem and progenitor cells in vitro and in vivo [36]. DMAMCL significantly suppresses the growth of leukemia cells in vitro and tumorigenesis in a zebrafish xenograft model in vivo [35].…”
Section: Discussionmentioning
confidence: 99%
“…DMAMCL is a novel agent that has an effect of anti-tumor growth and anti-inflammation. DMAMCL reduces tumor proliferation in glioma cells in vitro and in vivo [23], and selectively deracinates AML stem and progenitor cells in vitro and in vivo [36]. DMAMCL significantly suppresses the growth of leukemia cells in vitro and tumorigenesis in a zebrafish xenograft model in vivo [35].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NF-κB in HSCs is low, while it is significantly over expressed in LSCs (36). Therefore, NF-κB could distinguish HSCs and LSCs, and may serve as a potential therapeutic target for the selective elimination of LSCs sparing HSCs (37,38).…”
Section: The Transcription Factors Of Lscs In Amlmentioning
confidence: 99%
“…DMAMCL (ACT001) was able to eliminate LSCs by inhibiting the activity of NF-κB. ACT001 was in clinical trial in Australia (36,40).…”
Section: The Transcription Factors Of Lscs In Amlmentioning
confidence: 99%
“…The expression of NF-kB in normal hematopoietic stem cells was low, while it was overexpressed significantly in leukemia stem cells [ 39 ]. Therefore, the expression and activity inhibition of NF-kB could be a potential therapeutic target for targeting leukemia stem cell.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NF-kB and NF-kB-regulated proteins such as p65, Bcl-2, XIAP, and FLIP played important roles in cell apoptosis. It was reported that parthenolide and micheliolide, with chemically reactive alpha-beta unsaturated lactone moiety, were able to covalently bind to proteins via the Michael acceptor and eliminate leukemia stem cell by inhibiting the activity of NF-kB [ 17 , 19 , 39 ]. We speculated that compounds with alpha-beta unsaturated lactone moiety might share some common protein targets.…”
Section: Discussionmentioning
confidence: 99%